2017
DOI: 10.1002/jor.23585
|View full text |Cite
|
Sign up to set email alerts
|

Center of pressure profiles in unilateral compared to bilateral end‐stage ankle osteoarthritis patients

Abstract: Ankle osteoarthritis (OA) compromises ankle joint stability in regards to static balance. Unilateral and bilateral osteoarthritis patients often exhibit different limb-loading patterns during static balance tasks. Symmetrical loading has been posited to improve balance performance. Therefore, the purpose of this study was to quantify balance performance in both ankle osteoarthritis patient groups. Twenty-two unilateral and twenty-one bilateral ankle osteoarthritis patients performed three 10-s quiet standing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(90 reference statements)
1
2
0
Order By: Relevance
“…20 Similarly, when comparing ankles with untreated osteoarthritis versus unaffected ankles, researchers found that the unaffected ankle compensated for deviations in anterior to posterior position and is relied upon to make postural adjustments. 14,33 These findings regarding differences in flexibility and balance are consistent with the perceptions of patients in this study.…”
Section: Discussionsupporting
confidence: 89%
“…20 Similarly, when comparing ankles with untreated osteoarthritis versus unaffected ankles, researchers found that the unaffected ankle compensated for deviations in anterior to posterior position and is relied upon to make postural adjustments. 14,33 These findings regarding differences in flexibility and balance are consistent with the perceptions of patients in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Gladish et al, studied center of pressure profiles in unilateral compared to bilateral end-stage ankle osteoarthritis patients. They suggested that center of pressure is a better measure of postural strategy while center of mass measures may be more representative of postural steadiness [ 43 ]. However, many authors use the COG measurement in assessing the statics of musculoskeletal biomechanics [ 9 11 , 31 – 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Little is currently known about the path of the COP in patients with ankle OA. There has been one analysis of COP during standing 27 and two during walking in OA patients using plantar pressure to quantify COP. 28,29 The former study reported that reduced loading under the heel and toes in ankle OA patients while the latter reported change in midfoot load in OA patients with surgical repair compared to healthy subjects.…”
mentioning
confidence: 99%